THE EFFECT OF SOLVENCY, COMPANY SIZE AND ACTIVITY ON PROFIT GROWTH IN MINING COMPANIES THAT ARE LISTED ON THE INDONESIA STOCK EXCHANGE FOR 2017-2021 PERIOD - RIA FEBRINA (Indragiri Research Center (ingreat), 2023)
This study aims to determine and obtain empirical evidence of the effect of solvency, company size and activity on profit growth in mining companies listed on the Indonesia Stock Exchange for the period 2017-2021. This research method uses a quantitative approach. The data collection technique is a questionnaire. The sample in this study used purposive sampling, namely 60 samples. The results of this study indicate that partially the solvency variable has no effect on earnings growth. The company size variable has no effect on earnings growth. Activity variables have no effect on earnings growth. Simultaneously solvency, company size and activity have no effect on earnings growth